1899
DOI: 10.1039/ct8997500640
|View full text |Cite
|
Sign up to set email alerts
|

LXII.—A study of the absorption spectra of isatin, carbostyril, and their alkyl derivatives in relation to tautomerism

Abstract: CadjostyriZ-(con tinued). 0.145 gram in 500 C.C. of alcohol. Thickness of layer of liquid in millimetres. Thiclrness of layer of liquid in millime tr es.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1909
1909
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The tautomeric equilibria of the pyridones have been studied extensively by many physical methods in the solid state and in solutions of various polarities (see citations in references [68,69,70]) and they indicate that in the condensed phase the equilibrium of 2-pyridone lies on the keto (lactam) side (by an indirectly measured enthalpy difference of 0.4 ± 0.6 kcal/mol [69]) and that 4-pyridone’s equilibrium is shifted to the enol (4-hydroxypyridine) side with an indirectly estimated enthalpy gap of 2.4 ± 0.6 kcal/mol [69]. Theoretical studies [68,69,70,71,72,73] also predicted a preference in the gas phase for the lactam form in the case of 2-pyridone (by ca . 1.7 kJ/mol), while the enol form for 4-pyridone was calculated to be more stable (by ca .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tautomeric equilibria of the pyridones have been studied extensively by many physical methods in the solid state and in solutions of various polarities (see citations in references [68,69,70]) and they indicate that in the condensed phase the equilibrium of 2-pyridone lies on the keto (lactam) side (by an indirectly measured enthalpy difference of 0.4 ± 0.6 kcal/mol [69]) and that 4-pyridone’s equilibrium is shifted to the enol (4-hydroxypyridine) side with an indirectly estimated enthalpy gap of 2.4 ± 0.6 kcal/mol [69]. Theoretical studies [68,69,70,71,72,73] also predicted a preference in the gas phase for the lactam form in the case of 2-pyridone (by ca . 1.7 kJ/mol), while the enol form for 4-pyridone was calculated to be more stable (by ca .…”
Section: Resultsmentioning
confidence: 99%
“…Then there is carbostyril: for more than a century this compound’s tautomerism has been under investigation [71,72,73]. The first assumption by A. Claus [71] in 1896 that the keto (lactam) form was dominant in solution rested on the analysis of its chemical selectivity towards bromination, an approach which nowadays, in view of today’s theoretical and practical knowledge about the reactivity/selectivity processes and kinetics of proton shifts, seems founded on pure speculation but was nonetheless correct as modern theoretical studies [73] confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…To trace the development, it is worth mentioning the first review devoted to absorption spectroscopy (from the UV to the IR region) in organic chemistry and particularly in elucidating structures of tautomeric compounds, written by Dobbie et al in 1921 [51]. According to this review, the first study using absorption spectroscopy was performed by Hartley and Dobbie [52] in 1899, who proved the constitution of isatin and other tautomeric compounds by comparison of their absorption curves with those of their nitrogen and oxygen methyl derivatives. In 1908, von Liebig [53] studied the fluorescence of organic dyes, some of which are tautomeric.…”
Section: Tautomeric Equilibrium: Historical Overview Of An Analyticalmentioning
confidence: 99%
“…UV-vis spectroscopy, being based on the interaction between light and mater, has always been related to color. And, naturally, it became the first instrumental method used to study tautomeric systems [2]. The main fundamental advantage of this method is that the electron excitation is much faster than the tautomeric proton exchange.…”
Section: Introductionmentioning
confidence: 99%